The Interaction of Public and Private Insurance: Medicaid and the Long-Term Care Insurance Market - Brown, Jeffrey R; Finkelstein, Amy (American Economic Review, 2008)
We show that even incomplete public insurance can crowd out private insurance demand. We estimate that Medicaid could explain the lack of private long-term care insurance for about two-thirds of the wealth distribution, even if no other factors limited the market's size. Yet Medicaid provides incomplete consumption smoothing for most individuals. Medicaid's crowd-out effect stems from the large implicit tax (about 60–75 percent for a median-wealth individual) that Medicaid imposes on private insurance. An implication is that public policies designed to stimulate the private insurance market will have limited efficacy as long as Medicaid's large implicit tax remains. (JEL G22, I18, I38)